The extent to which male and female teachers of Geography in Aqaba schools in Jordan possess some modern teaching skills - Alnjadat, Mohammed Hussein; Alzlabiah, Mahmoud Mohammed (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the extent to which teachers of geography in the schools of Aqaba Governorate in Jordan possess some modern teaching skills. Where an analytical descriptive approach was used, and a tool was designed to measure the extent of possessing modern teaching skills, consisting of five areas: (evaluation, teaching strategies, general principles, student, and teacher) and the study tool consisted of (29) paragraphs, applied to a random sample Of the teachers in Aqaba governorate schools in Jordan, they numbered (114) male and female teachers, and using the SPSS program in data analysis, the results of the study showed the following: - The overall level of the tool has been obtained: the degree of geography teachers’ possession of some modern teaching skills in Aqaba Governorate schools has a total average of (2.59 out of 3), i.e. a degree (high), and at the level of fields; the field of concepts related to the learner got the highest average (2.66) From 3) followed by concepts related to teaching strategies with an average of (2.64) then concepts related to the roles of evaluation; with an average of (2.60) then concepts related to general principles (2.57) and finally concepts related to the teacher (2.57) and all of them with a high rating. - The study concluded that there are statistically significant differences to the degree that geography teachers possess modern teaching skills due to the gender variable, in favor of males, and according to the variable of experience, and in favor of their lower experience, while there were no differences attributed to the variable of the academic qualification.